Impact of Corporate Social Responsibility Practices on the Financial Performance of Microfinance Institutions in Togo - Akouvi Gadedjisso-Tossou; Curwitch P’ham Bodjona; Maman Tachiwou Aboudou; Jean-Pierre Gueyie (New Innovations in Economics, Business and Management Vol. 10, 2022)
Microfinance has two goals: to alleviate poverty (social performance) and to ensure long-term profitability (financial performance). In addition to these two aspects, microfinance institutions (MFIs) have a social responsibility to their stakeholders. Corporate social responsibility (CSR) practices have gained interest across many firms, including MFIs. Several benefits are advocated (e.g., employee attraction and loyalty, customer retention, enterprise reputation), but CSR also induces increased costs. Thus, the main objective of this article is to measure the impact of the CSR practices of Togolese MFIs on their financial performance (FP). Using principal component analysis and partial least squares techniques, the analysis is carried out on a sample of 60 Togolese MFIs. When measured by the return on assets (ROA), the results demonstrate that CSR has a positive and substantial impact on the financial performance of MFIs through the dimensions of customers, employees, and community, but the environmental dimension has a negative significant impact. Given the collective increased interest in environmental issues, education programs and government policies need to be developed and implemented to change the view that environmental efforts and expenses are an irrelevant cost.